Late-Holocene record of lagoon evolution, climate change, and hurricane activity from southeastern Cuba. (September 2015) - Peros, Matthew; Gregory, Braden; Matos, Felipe; Reinhardt, Eduard; Desloges, Joseph
A sediment core from a lagoon in southeastern Cuba was the focus of a multi-proxy paleoenvironmental study to investigate lagoon response to sea-level change and climate change and also to infer changes in the frequency of past hurricane strikes. The proxy data examined included benthic foraminifera, fossil pollen, particle size analysis, and macrocharcoal influx values. The core was dated using 137 Cs and accelerator mass spectrometry (AMS) radiocarbon methods. The results show that lagoon formation began approximately 4000 years ago and that the lagoon environment evolved through four phases: (1) from 4000 to 2800 cal. yr BP, the lagoon was a shallow polyhaline to euryhaline system with limited mangrove coverage; (2) from 2800 to 2000 cal. yr BP, there was a decrease in salinity which facilitated the expansion of red mangrove; (3) from 2000 to 1000 cal. yr BP, sea-level rise resulted in an increase in water depth and possibly salinity; and (4) from 1000 cal. yr BP to the present, water level continued to rise and the mangrove environment diversified. The shift to lower salinity conditions from 2800 to 2000 cal. yr BP may have been climate driven as similar changes are seen at lagoons elsewhere in Cuba. The particle size data show several periods where sand-sized particles are more abundant; these periods are similar to data from Puerto Rico that document times of relatively frequent hurricanes. This paper shows that coastal lagoons are useful archives of paleoclimatic and paleoenvironmental information in the Caribbean region and that they should be the focus of additional research efforts.